2013
DOI: 10.1128/iai.00113-13
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus and Streptococcus suis Capsular Polysaccharides Induce Chemokine Production by Dendritic Cells via Toll-Like Receptor 2- and MyD88-Dependent and -Independent Pathways

Abstract: bStreptococcus agalactiae (also known as group B Streptococcus [GBS]) and Streptococcus suis are encapsulated streptococci causing severe septicemia and meningitis. Bacterial capsular polysaccharides (CPSs) are poorly immunogenic, but anti-CPS antibodies are essential to the host defense against encapsulated bacteria. The mechanisms underlying anti-CPS antibody responses are not fully elucidated, but the biochemistry of CPSs, particularly the presence of sialic acid, may have an immunosuppressive effect. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 91 publications
3
50
1
Order By: Relevance
“…Using highly purified CPS from S. suis type 2 containing less than 1% (wt/wt) of proteins or nucleic acids (as previously described by Calzas et al [30]), we investigated whether conjugation to a carrier protein, such as TT, would circumvent the TI antigenicity of the CPS and instead induce a TD protective humoral response in animals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using highly purified CPS from S. suis type 2 containing less than 1% (wt/wt) of proteins or nucleic acids (as previously described by Calzas et al [30]), we investigated whether conjugation to a carrier protein, such as TT, would circumvent the TI antigenicity of the CPS and instead induce a TD protective humoral response in animals.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its high M w , found to be between 410,000 and 480,000 Da by SEC-MALS (28,30), the native polysaccharide of S. suis type 2 must first be depolymerized into smaller fragments. This reduces polydispersity and yields higher ratios of polysaccharide to protein following coupling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Encapsulated GBS interaction with lipid rafts might also facilitate bacterial contact with caveolin-1, leading to modulation of caveolin-related signaling pathways and activation of specific immune mediators, for instance CCL2 [37] . We also observed that highly purified GBS CPSs induced significant production of CCL3 by DCs, via partially TLR2-and myeloid differentiation factor 88 (MyD88)-dependent pathways, and CCL2, via TLR-independent mechanisms [38] . A similar pattern was observed with highly purified S. suis CPSs.…”
Section: Research Highlight Highlightmentioning
confidence: 66%